296 Genetic and genomic analysis of vulva size in Landrace and Yorkshire gilts. (7th December 2018) - Corredor, F; Leach, R; Ross, J; Keating, A; Serão, N
Abstract: Reproductive performance is critical for efficient swine production. A relationship between the size of the vulva measured in gilts prior to puberty at 15 weeks of age and subsequent reproductive performance has been demonstrated. The objective of this study was to estimate genetic parameters and perform genomic analysis on vulva size traits. A total of 1411 animals from Landrace (n=587) and Yorkshire (n=824) breeds were used for this trial. Measurements including vulva width (VW), vulva height (VH), and vulva area (VA) were taken at an average age of 21.5 weeks. Genotype data (Geneseek GGP-HD) was available for all animals by imputation. Genetic parameters were estimated using measurement week, breed, line, and body weight (covariate) as fixed effects in an animal model. For genomic analyses, BayesCp was used to estimate the p to be used in genome-wide association (GWA) analyses using BayesB. Heritability estimates for both breeds grouped were 0.42 ± 0.08, 0.26 ± 0.06, and 0.41 ± 0.07 for VA, VW, and VH, respectively. Estimates of genetic correlations were 0.93 ± 0.02 between VA and VH, 0.95 ± 0.02 between VA and VW, and 0.78 ± 0.08 between VH and VW. The GWA analyses identified QTL associated with vulva measurements. For VH in Landrace, a QTL located on Sus scrofa chromosome (SSC) 7 at 107Mb accounted for 9% of the genetic variance. This region harbors FLRT2, a gene that regulates early embryonic vascular development. For VW in Landrace, a QTL on SSC2 (154Mb) and SSC8 (60Mb) explained 4% and 1.5% of the genetic variance, respectively. For VW in Yorkshire, a QTL on SSC2 (28Mb) explained 2% of the genetic variance. Our results support a large genetic variability for vulva measurements at approximately 21.5 weeks of age and that a genomic region on SSC7, including a gene associated with embryonic development, accounts for 9% of genetic variability for VH in Landrace gilts.